2001
DOI: 10.1071/wf01018
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrate assemblages in five central Idaho (USA) streams over a 10-year period following disturbance by wildfire

Abstract: e t a l .S t r e a m m a c r o i n v e r t e b r a t e s o v e r 1 0 y e a r s f o l l o wi n g w i l d f i r e W F 0 1 0 1 8 G . W a y n e M i n s h a l l , C h r i s t o p h e r T . R o b i n s o n , D e r o n E . L a w r e n c e , D o u g l a s A . A n d r e w s a n d J a m e s T . B r o c kAbstract. The effects of wildfire on benthic macroinvertebrate assemblages of streams in mixed-conifer forest were examined for 10 successive years following the Mortar Creek Fire of 1979. Changes in burned-catchment str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 14 publications
(25 reference statements)
5
56
1
Order By: Relevance
“…The continued divergence of the BMI community from pre-fire conditions and deteriorating in-stream biotic conditions indicate that the resilience of BMI communities to environmental stress in Angora Creek may have declined further in the second year, although that decline may have begun to reverse during our last sampling period (August 2009). Longer-term studies have observed that in small streams with well-managed and intact watersheds, divergence from pre-fire conditions may persist from 1 to 10 years, and high within-year variability may continue for an unknown ([15 years) length of time (Roby & Azuma, 1995;Mihuc et al, 1996;Minshall et al, 2001b, c). We report significant community changes for at least 2 years following the Angora fire, but further sampling is needed to determine if recovery indeed began in August 2009.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The continued divergence of the BMI community from pre-fire conditions and deteriorating in-stream biotic conditions indicate that the resilience of BMI communities to environmental stress in Angora Creek may have declined further in the second year, although that decline may have begun to reverse during our last sampling period (August 2009). Longer-term studies have observed that in small streams with well-managed and intact watersheds, divergence from pre-fire conditions may persist from 1 to 10 years, and high within-year variability may continue for an unknown ([15 years) length of time (Roby & Azuma, 1995;Mihuc et al, 1996;Minshall et al, 2001b, c). We report significant community changes for at least 2 years following the Angora fire, but further sampling is needed to determine if recovery indeed began in August 2009.…”
Section: Discussionmentioning
confidence: 71%
“…In general, larger effects tend to be observed in small, first-order streams, similar to Angora Creek (Minshall et al, 2001b, c;Hall & Lombardozzi, 2008). This study provides information on the short-term effects of a severe fire on high-elevation aquatic benthic macroinvertebrates in the context of low precipitation years.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Among other factors, gene flow may have provided an important buffer against expected losses of genetic variability in the face of both historical and recent population reductions. The natural landscape of the Middle Fork Salmon River is dynamic, with massive landslides (Meyer and Leidecker 1999), wildfires (Minshall et al 2001), and climatic extremes influencing habitats and, undoubtedly, populations of Chinook salmon. In more recent decades, changes to migration corridor habitats outside the MFSR, combined with the influences of harvest and hatchery propagation, have likely contributed to population declines across the Columbia River basin (McClure et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…The 1988 fi res were a major disturbance event, consuming over 45 % of the 2 million ha Yellowstone park landscape (Schullery, 1989). Modifi cation of trophic pathways is one of the many ecosystem responses to wildfi re disturbance along with altered channel morphology, nutrient dynamics, sediment suspension, leaf litter input, and changes in the composition of aquatic biota (Minshall et al, 1989;1997;2001a;2001b;Mihuc et al, 1996;Robinson and Min-542 T. B. Mihuc and G. W. Minshall Stream foods webs after wildfi re disturbance shall, 1996). In the fi rst decade after wildfi re Yellowstone streams exhibited elevated nitrate levels, increased channel alteration, increased periphyton biomass (after the fi rst two years), higher summer water temperature and, of course, an increase in the amount of available burned organic material as carbon (Minshall et al, 1997;2004).…”
Section: Introductionmentioning
confidence: 99%